Association between prior extracurricular publications and the intent of students publishing their theses in scientific journals: A Cross-Sectional Study of 40 Medical Schools in Latin America - Valladares-Garrido, Mario J. (2020)
Aimm:To determine the association between prior extracurricular publication and the intention of medical students in Latin America publishing theses in scientific journals. Methods: Cross-sectional study, where the main variable was the intent to publish a thesis, investigatingan association with prior extracurricular publication and other co-variables of interest. Prevalence ratios (PR) were estimated using generalized linear multilevel models. Results:Of 11,587, 7.9% self-reported previous publications and 2,9% had interest inpublishing their thesis. We found that having previously published, increased the intention to publish a thesis in scientific journals (PR: 6.72, 95% CI: 5.12-8.84, p <0.001). Also positively associated with publishing a thesis included; being Peruvian (PR: 1.80, IC95%: 1.08-2.98, p = 0.023), being female (PR: 1.24, IC95%: 1.00-1.54, p = 0.046), being afifth year student (PR: 2.26 , 95% CI: 1.55-3.29, p <0.001), havingan intermediate proficiency of the English language (PR: 1.62, 95% CI: 1.14-2.32, p = 0.008) and database training (PR: 1.58, 95% CI 1.14-2.18, p = 0.005). Conclusion:The intention of publishing theses in scientific journals is very low,however, having prior extracurricular publications increases the level of interest. These findings provide medical schools with information that will enable them to help reinforcethe student’senthusiasmto publish and, thereby, greatlyincrease their decision to complete and publish a thesis.